ChemInform Abstract: Aza‐Nickelacycle Key Intermediate in Nickel(0)‐Catalyzed Transformation Reactions. Issue 34 (August 2015) - Ohashi, Masato; Hoshimoto, Yoichi; Ogoshi, Sensuke
Abstract Review: 92 refs.